Disiplin Belajar Dan Kreativitas Terhadap Hasil Belajar Siswa Teknik Gambar Bangunan SMK Negeri 3 Tahuna - Abast, Rio Metry; Kembuan, Djubir R.E. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze: (1) The influence of learning discipline on learning outcomes of State Vocational High School 3 Tahuna. (2) The influence of learning creativity on learning outcomes of students of State Vocational High School 3 Tahuna. (3) The influence of learning discipline and learning creativity simultaneously on learning outcomes of students of State Vocational High School 3 Tahuna. This study was conducted at State Vocational High School 3 Tahuna. The design of this study is quantitative research with a correlational research approach, using simple regression analysis and multiple regression. From the results of the study: 1) there is a significant influence between learning discipline on student learning outcomes, contributing 34.40%; 2) there is a significant influence between learning creativity on student learning outcomes, contributing 21.60%; 3) there is a significant influence between work discipline and learning creativity simultaneously with student learning outcomes, contributing 37.50%. Thus, increasing learning discipline and competent learning creativity will have the form of discipline in going to school; discipline in following lessons at school; discipline in doing assignments; discipline in studying at home; Discipline in adhering to school rules; curiosity, imagination, originality in expressing ideas, the ability to see problems from various perspectives; and a courageous attitude to take risks will improve learning outcomes in terms of changes in attitudes, morals, and intelligence. With a conducive learning discipline and creativity, it is hoped that it will provide maximum learning outcomes for students. In other words, high levels of learning discipline and creativity will foster good and high student learning outcomes.